Marketing Plan Implementation over Business Start-up: Food Combining at PT. BERAS JAGUNG NUSANTARA - Muhammad Rully Firmansyah; Tantri Yanuar Rahmat Syah; Semerdanta Pusaka; Dadan Ramdhani (Journal of Multidisciplinary Academic, 2020)
This research aimed to make the business activity to be conducted with accordance a plan and also to find out the position of company this time, direction of the company’s goals and how to achieve the market target. The result shows a company tries to offer Food Combining product which is different with product existed in the market (both from the taste, quality, or affordable price). Here, the operational activities of market company are really possible to be run so that company can offer more competitive price compared to import products that have entered the market. The increase of market share taken by PT. Beras Jagung Nusantara become is very significant with constant increase value per year 5% then in the end of the fifth year. Furthermore, PT. Beras Jagung Nusantara have a target to take market share amounted 25% from company planning elaboration and analysis. Thus, this company can be worth running and promising a business.